THE ROLE OF EXTRACURRICULAR ACTIVITIES IN FOSTERING YOUTH RESPONSIBILITY AND LEADERSHIP: A LITERATURE REVIEW - Sri Andayani (Indonesian Journal of Education and Youth Development, 2025)
This study aims to explore the relationship between participation in extracurricular activities and the development of responsibility and leadership among high school students. Using a qualitative approach involving observations and interviews with active students, the research reveals that involvement in extracurriculars significantly enhances social skills, decision-making ability, and self-awareness. Furthermore, such engagement provides real opportunities for students to practice leadership in a supportive context. The findings highlight the vital role of extracurricular programs in shaping character and leadership competence in the younger generation.